Augustine : political writings - Atkins, E. M. (E. Margaret); Dodaro, Robert, 1955- (Cambridge texts in the history of political thought., 2001)
This collection brings together thirty-five letters and sermons of Augustine, Bishop of Hippo from 396 to 430 AD, that deal with political matters. The letters and sermons are both practical and principled and treat many essential themes in Augustine's thought, including the responsibilities of citizenship, the relationship between the church and secular authority, religious coercion, and war and peace. These texts complement Augustine's classic The City of God against the Pagans (also available in the Cambridge Texts series), and give students direct insight into the political and social worl.